Generation of a Dynamical Logic Gate From Unstable Dissipative Systems of Type 1 - Rivera-Durón, Roberto R.; Sevilla-Escoboza, Ricardo; Wang, Qui-Ling (Frontiers in Applied Mathematics and Statistics, 2022)
The obtainment of a dynamical logic gate, which is a device capable of implementing several logic functions using the same model, has been one of the goals of the scientific community. Dynamical systems, specifically those that display chaotic behavior, have been widely used to emulate different logic gates which are the basis of general-purpose computing. In this work, we present a methodology based on unstable dissipative systems of type 1, a kind of dynamical system capable of generating multi-scrolls and multi-stability. Using these two features, we codify inputs, subsequently, we get the adequate output, developing in this way a dynamical (reconfigurable) logic gate that performs any of the sixteen possible logic functions of two inputs. A highlight of the proposed methodology is that the selection of the desired logic gate is realized just varying a couple of parameters.